Case study on symptoms and the relationship of side effects on patient abandonment during leprosy treatment carried out in a Palmas-TO (Research, Society and Development, 2021)
Leprosy is a notifiable chronic infectious disease, transmitted through the airways through the etiological agent mycobacterium leprae. In this sense, this study aims to use a questionnaire on symptoms, treatment, sequelae and care in the Unified Health System (SUS), and to correlate the results obtained with the therapeutic relationship used with the abandonment of patients during treatment by a family group from the city of Palmas -TO. Among the 10 participants in the family group, only eight effectively answered the questionnaire. The data obtained show that despite the various campaigns made available by the government, the diagnosis of the disease is still late, as most patients only look for a medical clinic after the disease worsens. Such data are reinforced by the answers obtained by the questionnaire applied as: of the total number of participants, only six had basic knowledge about the disease, but only one sought the health center, two had no knowledge about the disease and seven sought only the health center because the diagnosis of a family member. All participants had aggravation of symptoms during treatment, among them, one participant had neurological problems that led to the use of antidepressants as an alternative treatment. Finally, one participant abandoned treatment due to social and therapeutic inconveniences, one participant is still undergoing treatment and five still feel pain or have psychological sequelae after treatment. The other participants report that they did not have sequelae right after the end of the treatment.